DETERMINAN PENYERAPAN ANGGARAN BELANJA SATUAN KERJA KEMENTERIAN NEGARA / LEMBAGA - Huda, Anas Nur; Pandaya, Pandaya (JURNAL AKUNTANSI, 2019)
Budget absorption is one of the drivers of economic growth through government consumption. For this reason, absorption of ministries / agencies' budgets also determines the economic growth. In addition, budget absorption becomes a dominant factor in evaluating bureaucratic performance. Failure to target budget absorption will indeed result in reduced spending benefits. Because the funds that have been allocated, apparently not all of them can be utilized which means there are funds that are idle cash. Even though if the budget allocation is efficient, despite the limited financial resources, the state can still optimize the funding of other strategic activities. This study aims to examine the effect of budget planning and budget execution on budget absorption. The questionnaire was distributed in the work units of state ministries / institutions in the payment area of KPPN Jakarta V with a budget absorption rate below 75% in 2017 according to the KPPN Level Budget Realization Report. The results of this study indicate that budget planning and budget execution have a positive effect on budget absorption.